CREATING A MATHEMATICAL ALGORITHM FOR TEAM SELECTION IN IT PROJECTS - ZOLOTUKHA, ROMAN; GLAZUNOVA, OLENA (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The article presents a study on the development of a mathematical algorithm for selecting an optimal team in IT projects. The relevance of the research lies in the fact that selecting the optimal team is a critical success factor in IT projects. The main objective of the study is to explore modern approaches to team formation and to define an optimal framework for team selection that contributes to successful project execution and efficient resource utilization. The article sets forth the following tasks: to analyze the theoretical and methodological foundations of economic-mathematical modeling for candidate selection in teams; to develop a model for forming collectives in IT projects. The model examined in this research is a multi-criteria optimization model with weighted coefficients. It enables the consideration of various criteria for team selection, such as profession, qualification, hard and soft skills of candidates, English language proficiency, personality type, and salary expectations. To achieve this, the authors utilized multi-criteria optimization methods as well as machine learning algorithms to determine weighted coefficients. The article presents the research results and describes the effectiveness of the multi-criteria optimization algorithm with weighted coefficients. Additionally, recommendations are provided in the article regarding the practical utilization of the model in team selection within the IT sector. The objective function is the maximization of team efficiency through scores obtained after adding weighted coefficients for each candidate. The outcome of the mathematical algorithm's work is the formation of a team that can be recommended for working on an IT project.
Keywords: mathematical model; team selection; IT projects; weighted coefficients; hard skills; soft skills; expert evaluations